STRATEGIC PLAN FOR ECONOMIC REACTIVATION IN THE GASTRONOMIC FIELD - Gissell Cáceres Mora, Clara; Vanessa Fernández Paredes, Luz; Jazmín Avalos Portillo, Pamela; Sosa, Vivían; María Luisa Martínez, Abog (Revista Gênero e Interdisciplinaridade, 2023)
In this final degree project called “Strategic plan for economic reactivation in the gastronomy sector,” whose objective is: Analyze the importance of the implementation of a strategic plan for economic reactivation in the gastronomic sector of Ciudad del Este. The qualitative approach was adopted as the study method, using the survey method directed at 30 managers or owners of the same. The responses were used to identify the challenges that gastronomic companies in Ciudad del Este face today, as well as point out the characteristics of the gastronomic market, investigate the strategies applied by gastronomic companies to reinvent themselves during the pandemic and therefore Lastly, the positive results that the application of a strategic plan in gastronomic companies will produce. In conclusion, it can be stated that the majority of the companies surveyed mention that thanks to the implementation of a strategic plan they were able to reactivate themselves economically.